Protocol for using organic persulfides to measure the chemical reactivity of persulfide sensors - Fakhoury, Joseph N. (2022)
Hydrogen sulfide (H2S) and downstream reactive sulfur species (RSS), including organic persulfides, protect bacterial cells against diverse oxidative stressors. Specialized dithiol-based transcriptional repressors sense persulfides directly to control cellular H2S/RSS and avoid toxicity. Here, we present a protocol to quantify the kinetics of chemical reactivity of cysteines in two bacterial persulfide sensors toward cysteine persulfide and glutathione persulfide, with a LC-ESI-MS analysis that results in a kinetic model. This protocol has potential applications to other cysteine-containing proteins and oxidants. For complete details on the use and execution of this protocol, please refer to Fakhoury et al. (2021) and Capdevila et al. (2021).